Implementation of Human Resources Strategy at Aston Tanjungpinang Hotel - Nurul Sultania; Melia Andriyani; Nur Dwi Apriliani; Feradha Nur Larasati; Satriadi Satriadi (International Journal of Economics and Management Research, 2025)
This study aims to analyze the implementation of human resources (HR) strategies at Aston Tanjungpinang Hotel. The method used was a qualitative approach with case studies and phenomenology, involving in-depth interviews with hotel managers and staff. Data was collected through purposive sampling, focusing on employee experiences related to training, career development, and performance management. The results showed that Hotel Aston implemented a comprehensive HR strategy, including competency-based recruitment, continuous training, and a good employee maintenance system. Nonetheless, challenges such as high employee turnover rates and competition from other industries remain a concern. This research concludes that effective HR management not only improves service quality, but also contributes to the long-term success of the hotel.